FÍSICA PARA TODOS: SITUAÇÕES DE APRENDIZAGENS EM UM SIMULADOR VEÍCULAR - Kürschner, Victor Noster; Toniazzo, Nelson Adelar; Japp, Mathias Rambo; Cargnelutti, Guilherme Antonello; Schonardie, Matheus Felke; Schmidt, Pedro (Salão do Conhecimento, 2018)
Projeto de extensão Física para todos